Urban agriculture and food security in the city of Lubumbashi (DRC). - Tambwe, Nyumbaiza (My University, 2010)
The aim of this study is to find out whether or not urban farming is a response to food insecurity in the post-Gécamines era at the household level. This period is characterized by acute economic crisis at a time of rapid population growth and increasing urban poverty. Data was collected by means of semi-structured interviews, in-depth questions, observation and informal conversation, as well as primary and secondary sources. One hundred Lubumbashi farming households were selected and interviewed between November 2004 and March 2005. The data was analyzed within a sustainable livelihood approach based on the alternative theories of development, and using SPSS and thematic content analysis. Because of its potential in food supply and income generation, the focus on urban agriculture gives in-depth insights about categories of people involved, types of food crops grown and livestock kept, relations within the household members, and so on. The key findings of the study are that urban agriculture is more of a survival-entrepreneurial strategy than a survival or an entrepreneurial strategy for the majority of farming households. Less than a quarter of the selected farmers were able to move out of food insecurity and poverty. However, the majority of farmers were food secure for a short period of time (three to four months, particularly at the harvest period). The study also shows that though the living conditions of the majority of farmers (75%) declined despite the practice of food production, these conditions might have worsened without it. iii Poverty, competition for land and rapid population growth constitute the factors that threaten the expansion of agricultural activities within and around the city. The sustainability of urban agriculture is linked to its capacity to cope with and recover from stresses and shocks as well as its adaptability to the dynamism of the city, and the nature of support received from state and non-state institutions. However, food production and income generation remain the central functions of urban agriculture in Lubumbashi. Keywords: urban agriculture, food security, urban livelihood strategy, sustainable livelihoods approach, sustainability, entrepreneurial urban agriculture, survival urban agriculture, alternative theories of development, household economy, parallel economy.